STRIVING for INCLUSIVE DEVELOPMENT : FROM PANGKOR TO A MODERN MALAYSIAN STATE - Nazrin Shah Ibni Sultan Azlan Muhibbuddin Shah, Raja, author (Selangor : Oxford University Press, 2019)
By the author of the highly acclaimed ?Charting the Economy?, this book is the most comprehensive study yet of Malaysia's impressive economic and social transformation over the past 150 years.0Drawing on primary data sources, archival documents and cutting-edge national and international research, Sultan Nazrin Shah traces in detail Malaysia's fascinating journey, starting from the signing of the seminal Pangkor Treaty in 1874, through British occupation to the present.0The author unearths the true roots of Malaysia's economic and social development-its people, their human capital and well-being, as well as economic structures-including how the British established institutions for the expansion of the lucrative tin and rubber trade, and how they encouraged labour immigration to support their economic ambitions.0The outbreak of World War II and the Japanese occupation forced the British to rethink their strategy for Malaya, which experienced a sequence of turbulent events through to the formation of Malaysia in 1963.0The 1960s saw solid economic growth, but it failed to benefit the bulk of the population, helping to trigger ethnic clashes. One response by the government was the start of redistributive policies and aggressive affirmative action, with the launch of the New Economic Policy in 1971.0Almost 50 years later, sustained rapid economic growth and a modernizing economy have led to fast-rising incomes, the ending of extreme poverty and the emergence of a sizeable middle class, despite setbacks during financial and economic crises.0?Striving for Inclusive Development? makes it clear that the country still faces huge and complex challenges. Building on its analysis of the past, this landmark book concludes with a forward-looking assessment of these challenges, and sets out Sultan Nazrin Shah's vision for an inclusive and sustainable future